An exploration of the interdependencies betweeen the real exchange rate and the size of the tradable sector in a small open economy (Cultura Económica, 2022)
The complex interdependences between the real exchange rates and the size of the tradable goods sector have not been fully explored in the existing literature. This article aims to full this gap by developing a neo-classical Australian general equilibrium model to further explore these linkages and to explain the impact of total factor productivity, factor endowments, terms of trade and debt services (net of transfers and/or aid flows) on the equilibrium real exchange rate and the size of the tradable sector. Measuring changes in the allocation of resources by changes in the share of tradable goods in GDP, we show that in addition to the well-known spending and resource movement effects, that there are four further separately identifiable effects, which we refer to as the extraordinary profit effect, the traded price effect, the expenditure movement effect and the debt substitution effect. The relative strengths of these additional effects help to determine the size of the tradable goods sector and hence the economic structure of a small open economy.